Strategi pemasaran multikanal dan pengaruhnya terhadap loyalitas nasabah bank syariah - Maulana, Muhammad Mudzakkir (Maliki Interdisciplinary Journal, 2025)
Islamic banking in Indonesia is growing rapidly in line with increasing public awareness of Islamic financial principles. However, amidst increasingly fierce competition and advances in digital technology, Islamic banks face challenges in maintaining customer loyalty. One important strategic approach is the use of multi-channel marketing, a strategy that combines various physical and digital channels to create a consistent and connected service experience.This paper reviews the concept of a multi-channel marketing strategy in Islamic banking, its impact on customer loyalty, and the challenges and opportunities in its implementation. Using a descriptive qualitative approach based on literature review, we found that integrating various marketing channels such as branches, mobile applications, internet banking, and social media can increase customer satisfaction and trust, which in turn strengthens loyalty.Furthermore, the success of this strategy is determined by the bank's ability to balance the integration of technology, human resources, and Sharia principles. Challenges such as the lack of digital infrastructure, limited Sharia financial literacy, and system integration costs need to be addressed through collaboration between regulators, financial institutions, and educational institutions. Therefore, a multi-channel strategy that is in line with Islamic values ​​not only increases marketing effectiveness, but also strengthens the image and public trust in Islamic banks.